Formation and Inhibition of Lipid Alkyl Radicals in Roasted Meat - Yingjie Bao; Yuxia Zhu; Xiaopu Ren; Yawei Zhang; Zengqi Peng; Guanghong Zhou (Foods, 2020)
Free radicals are ubiquitous in roasted foods. In this work, lipid-derived carbon-centered alkyl radical formation was first studied in roasted meat by electron spin resonance (ESR). The influence of antioxidants on the inhibition of free radicals was investigated. The results showed that the high temperature, high heat transfer rate, and high polyunsaturated fatty acid (PUFA) content resulted in high radical content in roasted meat, while the high water content in meat retarded radical formation. The 0.03% addition of tea polyphenols (TPP) significantly reduced radical formation during roasting (p < 0.05), whereas the 0.03% rosemary extract (RE) had no significant inhibitory effect (p > 0.05). These results suggested that water retention and the addition of TPP would decrease radical generation during the roasting of meat.